First record of Leucoagaricus nivalis from Pakistan - Jabeen, Sana; Waseem, Bushra; Tuba, -; Hamid, Mughees; Yasmeen, Aneela (Bangladesh Journal of Plant Taxonomy, 2020)
Abstract not available Bangladesh J. Plant Taxon. 27(2): 453-459, 2020 (December)